Dzihunia pseudoamudarjensis, a new nemacheilid loach from the Syr Darya drainage (Teleostei: Nemacheilidae) - Sheraliev, Bakhtiyor; Kayumova, Yorkinoy (Zootaxa, 2024)
Dzihunia pseudoamudarjensis, new species, is described from the middle portion of the Great Fergana Canal in the Fergana Valley. The new species is distinguished from its congeners by having a complete lateral line with 84–86 pores, a slenderer caudal peduncle, a smaller dorsal and anal fin depth, and a wider interorbital distance. A key to Dzihunia species is provided.